The Target MicroRNAs and Potential Underlying Mechanisms of Yiqi-Bushen-Tiaozhi Recipe against‐Non-Alcoholic Steatohepatitis - Hong, Wei; Li, Songsong; Cai, Yueqin; Zhang, Tingting; Yang, Qingrou; He, Beihui; Yu, Jianshun; Chen, Zhiyun (Frontiers in Pharmacology, 2020)
MicroRNAs (miRNAs) have emerged as potential therapeutic targets for non-alcoholic fatty liver disease/non-alcoholic steatohepatitis (NAFLD/NASH). Traditional Chineses Medicine (TCM) plays an important role in the prevention or treatment of NAFLD/NASH. However, miRNA targets of TCM against NASH still remain largely unknown. Here, we showed that Yiqi-Bushen-Tiaozhi (YBT) recipe effectively attenuated diet-induced NASH in C57BL/6 mice. To identify the miRNA targets of YBT and understand the potential underlying mechanisms, we performed network pharmacology using miRNA and mRNA deep sequencing data combined with Ingenuity Pathway Analysis (IPA). Mmu-let-7a-5p, mmu-let-7b-5p, mmu-let-7g-3p and mmu-miR-106b-3p were screened as the main targets of YBT. Our results suggested that YBT might alleviate NASH by regulating the expression of these miRNAs that potentially modulate inflammation/immunity and oxidative stress. This study provides useful information for guiding future studies on the mechanism of YBT against NASH by regulating miRNAs.